1999
DOI: 10.1073/pnas.96.15.8534
|View full text |Cite
|
Sign up to set email alerts
|

Natural 13 C abundance reveals trophic status of fungi and host-origin of carbon in mycorrhizal fungi in mixed forests

Abstract: Fungi play crucial roles in the biogeochemistry of terrestrial ecosystems, most notably as saprophytes decomposing organic matter and as mycorrhizal fungi enhancing plant nutrient uptake. However, a recurrent problem in fungal ecology is to establish the trophic status of species in the field. Our interpretations and conclusions are too often based on extrapolations from laboratory microcosm experiments or on anecdotal field evidence. Here, we used natural variations in stable carbon isotope ratios (␦ 13 C) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
168
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(185 citation statements)
references
References 14 publications
16
168
1
Order By: Relevance
“…Similar results were obtained by other researchers (HOB-BIE et al 2000;GARTEN 1993). Foliar δ 15 N should reflect the δ 15 N of soil N sources when N is limiting (HÖGBERG 1997;HÖGBERG et al 1999). The decreasing foliage 15 N with altitude might be attributed to the net nitrification potential in soil, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by other researchers (HOB-BIE et al 2000;GARTEN 1993). Foliar δ 15 N should reflect the δ 15 N of soil N sources when N is limiting (HÖGBERG 1997;HÖGBERG et al 1999). The decreasing foliage 15 N with altitude might be attributed to the net nitrification potential in soil, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in various temperate forest ecosystems have shown that a distinction can be made between ectomycorrhizal and saprotrophic basidiomycetes, with the former showing depletion of 13 C compared to the latter (22,25,27). This difference has been proposed as a diagnostic tool for these two major basidiomycete functional groups (22,25,27). Our results suggest a The original fungal inoculum contained less than 0.5 ϫ 10 Ϫ6 g of C. b The amount of respired CO 2 was estimated by using the average ratio of CO 2 to fungal biomass obtained in closed systems (0.722) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, when ecosystems are transformed from C 3 -dominant vegetation to C 4 -dominant vegetation, the relative abundance of stable C isotopes in the soil is roughly maintained and is similar to that in the original vegetation, suggesting that only minor changes due to microbial transformations occur (5, 43). Nevertheless, more detailed measurements of C isotopic distributions have revealed patterns that suggest that significant discrimination by microbes occurs during soil formation; these patterns include the consistent enrichment of 13 C often observed with increasing depth in soil profiles (34) and the relative enrichment observed in the CO 2 produced from soil respiration compared with canopy measurements (12, 13).More directly, recent studies of fungi indicate that significant isotopic effects can be apparent when fungal tissues are compared to their presumed plant substrates (20,22,24,25,27,44,45), and a consistent difference in isotopic fractionation between mycorrhizal and saprotrophic basidiomycetes has also been found in the field (22,25,27). Given the importance of fungi in terrestrial ecosystems (15,35,40), the implications of isotopic discrimination associated with fungal C processing are of great consequence for isotope-based nutrient cycling models.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…was the most frequently occurring fungal species in this area. This species was earlier classified on the basis of its phylogenetic analysis as a saprobiont (Matheny et al, 2006), although there are reports indicating that it belongs to the ectomycorrhizal fungi (Högberg et al, 1999).The collected fungus strain was identified on the basis of ITS sequence in accordance with the procedure given by Hrynkiewicz et al (2010). A phylogenetic analysis of these sequences is presented in Fig.…”
Section: Microbial Materials and Culture Conditionsmentioning
confidence: 99%